2019
DOI: 10.1101/848135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of Cas9/dCas9 associated toxicity in microbes

Abstract: 23The CRISPR-Cas9 system has been used extensively in eukaryotic and prokaryotic systems for 24 various applications. In case of the latter, a couple of previous studies had shown Cas9 protein 25 expression associated toxicity. We studied the same in five microbes, viz Escherichia coli, 26 Salmonella typhimurium, Mycobacterium smegmatis, Xanthomonas campestris and 27 Deinococcus radiodurans. Transformation efficiency of plasmids carrying genes coding for 28 Cas9 or dCas9 was used to gauge toxicity associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…By contrast, the non-specific TAP-dCas9-nsp add no effect on curli formation or aggregation in the OmpR234 strain. Besides, we confirmed that the constitutive production of the Cas9 or dCas9 from the TAPs do not cause growth defects (Supplementary Fig.1d) or elongated cell morphology (Supplementary Fig.1e), contrasting with the toxic effects reported in some systems 15–18 . These results demonstrate that TAPs ability to induce Cas9-mediated killing or dCas9-mediated gene expression inhibition is efficient and depends on the accurate targeting by the spacer sequence.…”
Section: Resultssupporting
confidence: 77%
“…By contrast, the non-specific TAP-dCas9-nsp add no effect on curli formation or aggregation in the OmpR234 strain. Besides, we confirmed that the constitutive production of the Cas9 or dCas9 from the TAPs do not cause growth defects (Supplementary Fig.1d) or elongated cell morphology (Supplementary Fig.1e), contrasting with the toxic effects reported in some systems 15–18 . These results demonstrate that TAPs ability to induce Cas9-mediated killing or dCas9-mediated gene expression inhibition is efficient and depends on the accurate targeting by the spacer sequence.…”
Section: Resultssupporting
confidence: 77%
“…In any case, they may have common drawbacks related to the continuous expression of a foreign Cas9 protein. SpCas9 overexpression can be highly cytotoxic in E. coli and many other bacteria (it will be explained within the next section) leading to little or no colonies, even when devoid of its nuclease activity [ 50 , 51 ].…”
Section: Crispr-cas9-based Methods For Genome Editing In Bacteriamentioning
confidence: 99%
“…Early findings have shown the potential for non-specific nuclease activity toxicity of the Cas9 protein. However, the idea must be amended in comparable toxicities with dCas9 [257]. On the other hand, a low dose of NCs including metals, oxides of metals, polymers, and composites is usually non-toxic, prolonged delivery of such agents can lead to long-term aggregation and potential toxicity.…”
Section: Toxicity Assessment With Reference To the Disease Modelsmentioning
confidence: 99%